Reciprocal Interactions between Breast Tumor and Its Adipose Microenvironment Based on a 3D Adipose Equivalent Model - Delort, Laetitia (Public Library of Science, 2013)
Breast cancer has become the most common cancer among women in industrialized countries. Obesity is well established as a risk factor, in particular owing to the attendant secretion of the entities called adipokines; there is growing evidence for a role of cells and factors present in the mammary tumor microenvironment such as fibroblasts, preadipocytes, adipocytes and their secretions. To study how the microenvironment influences breast cancer growth, we developed a novel tridimensional adipose model epithelialized with normal human keratinocytes or with breast cancer cell lines. These mimicked a breast tumor in contact with an adipose microenvironment and allowed monitoring of the interactions between the cells. Leptin and adiponectin, two major adipokines, and their respective receptors, ObRt and AdipoR1, were expressed in the model, but not the second adiponectin receptor, AdipoR2. The differentiation of preadipocytes into adipocytes was greater when they were in contact with the breast cancer cell lines. The contact of breast cancer cell lines with the microenvironment completely modified their transcriptional programs by increasing the expression of genes involved in cell proliferation (cyclinD1, MAPK), angiogenesis (MMP9, VEGF) and hormonal pathways (ESR1, IL6). This tridimensional adipose model provides new insights into the interactions between breast cancer cells and their adipose microenvironment, and provides a tool to develop new drugs for the treatment of both cancer and obesity.